2019
DOI: 10.1186/s13075-018-1770-1
|View full text |Cite
|
Sign up to set email alerts
|

The circadian regulator Bmal1 in joint mesenchymal cells regulates both joint development and inflammatory arthritis

Abstract: BackgroundThe circadian clock plays a crucial role in regulating physiology and is important for maintaining immune homeostasis and responses to inflammatory stimuli. Inflammatory arthritis often shows diurnal variation in disease symptoms and disease markers, and it is now established that cellular clocks regulate joint inflammation. The clock gene Bmal1 is critical for maintenance of 24-h rhythms and plays a key role in regulating immune responses, as well as in aging-related processes. Fibroblast-like synov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
4
36
0
Order By: Relevance
“…1). As before two distinct macrophage populations, defined by MHC II expression 21,22 , were found in the joints (Fig. 1a).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…1). As before two distinct macrophage populations, defined by MHC II expression 21,22 , were found in the joints (Fig. 1a).…”
Section: Resultssupporting
confidence: 72%
“…Circadian variation in disease severity is frequent, but the mechanisms explaining this are undefined. Circadian disruption through genetic targeting of the core clock genes Cry1/2 or Bmal1 is associated with aggravated disease in the more simplistic mouse model of arthritis, collagen antibody-induced arthritis (CAIA) 22,33 , providing evidence for the role of the clock in restraining the pathogenesis of this disease. Analysis of joint-derived macrophages and neutrophils revealed significant dampening of intrinsic clocks in these inflammatory cells under arthritic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that high melatonin concentrations in RA patients may modulate ROR activation [15]. ROR acts as a negative regulator of inflammation via the NF-κB signaling pathway and is essential in the activity of both melatonin and the clock gene Bmal1, which helps to maintain 24-h rhythms and regulate immune responses [15,37]. Moreover, ROR proteins bind into the promoter region and drive Bmal1 gene expression [38].…”
Section: Modulation Of the Circadian Clock By Melatonin In Ramentioning
confidence: 99%
“…A study by Haas et al demonstrated that FLS from OA and RA did express clock genes, but their expression was arrhythmic [10]. Hand and colleagues, however, were able to implicate FLS circadian rhythm in disease onset/progression by showing that FLS cells are indeed rhythmic and that the loss of circadian clock rhythm not only impacts their ability to regulate the inflammatory response, but also leads to worse disease progression in a model of arthritis [1]. However, given that Bmal1 was inactivated in all Col6a1-expressing cells throughout the development of the animal, it remains difficult to dissect what proportion of the observed effects were due to the loss of Bmal1 during developmental processes vs. post-induction of arthritis.…”
mentioning
confidence: 99%